Effect of the stearic acid-modified TiO2 on PLA nanocomposites: Morphological and thermal properties at the microscopic scale. Issue 6 (December 2021) - Deghiche, Amani; Haddaoui, Nacerddine; Zerriouh, Ali; Fenni, Seif Eddine; Cavallo, Dario; Erto, Alessandro; Benguerba, Yacine
Abstract: In this work, a route is developed to synthesize nanocomposites based on polylactic acid (PLA) and stearic acid-modified TiO2 nanoparticles (TiO2 -SA). The nanocomposite is prepared in two steps by solution and melt methods. Fourier Transform Infrared Spectroscopy (FTIR), X-ray Diffraction (XRD), Differential Scanning Calorimetry (DSC), as well as Thermogravimetric Analysis (TGA) are used to characterize the synthesized materials. Quantum chemical calculations are carried out by means of density functional theory (DFT) calculations, Blends study and AIM analysis, to investigate the role of Stearic Acid (SA) on the nanocomposite PLA/TiO2 at microscopic level. FTIR analysis confirms the functionalization of TiO2 nanoparticles by stearic acid (SA). The DSC results illustrates the overall TiO2 effect in reducing the glass transition temperature Tg (from 58° to 52 °C) and the rise in the crystallinity degree (from 0.19° to 7.18 °C) where the 5% of nanoparticle shows the optimum result. This could be attributed to the fact that TiO2 -SA acts as a nucleating agent, as confirmed also by XRD patterns. TGA analysis shows that the thermal stability of PLA decreases by the addition of TiO2 -SA and this effect is monothonic with TiO2 content where the 1% nanoparticle shows the most thermally stable formulation. Simulations at atomic level confirmed the dispersion of treated TiO2 in the matrix. In particular, SA plays the role of electron donor with PLA and TiO2, increasing the miscibility between them by a strong hydrogen bond. The main results obtained allow considering SA as a valid option for the functionalization of TiO2 before inclusion in PLA matrix. Graphical Abstract: ga1 Highlights: A nanocomposites PLA-TiO2 functionalized by stearic acid. The FTIR analysis showed an interaction between the organic and inorganic phases. XRD analysis concluded that PLA exhibited an amorphous state. The DSC results showed that the thermal transition temperatures decreased while the rate of crystallization increased. TGA demonstrated that the functionalized TiO2 decreases the thermal stability of the matrix.